Tanytarsus van der Wulp (Chironomidae, Diptera): new species from the western Amazon region in Peru and Brazil, new records from the Neotropics, and remarks on the taxonomy of the genus - Dantas, Galileu P.s.; Hamada, Neusa; Giłka, Wojciech (Zootaxa, 2023)
This research is focused on the diversity and systematics of Neotropical non-biting midges of the genus Tanytarsus van der Wulp, 1874, based on specimens collected from pristine areas of the western Amazon region in Peru and Brazil. Six new species are described: Tanytarsus aries sp. nov. (Peru), T. chicomendesi sp. nov. (Brazil, Acre), T. kaxinawa sp. nov. (Brazil, Acre; Peru), T. pinedoi sp. nov. (Peru), T. serra sp. nov. (Peru), and T. frameatus sp. nov. (Peru), the latter placed in the Tanytarsus hastatus species group, here defined. Data on several recently described Neotropical Tanytarsus, obtained by analyzing specimens recorded from different regions of Brazil (Amazonas, Bahia, Federal District, Pará, São Paulo, Tocantins) are appended, and remarks on the taxonomy and variations of their diagnostic structures are provided. Tanytarsus pollicis Reis, Lin et Ferreira-Keppler, 2022 is treated as a new synonym of Tanytarsus insolens Dantas et Giłka, 2017. Further two species, Tanytarsus marianae Reis, Lin et Ferreira-Keppler, 2022 and Tanytarsus rafaeli Reis, Lin et Ferreira-Keppler, 2022 are placed in the Tanytarsus kiche group. The Tanytarsus curvicristatus group is also supplemented with Tanytarsus giovannii Sanseverino et Trivinho-Strixino, 2010.